Factores socio epidemiologicos y el afrontamiento del paciente en cirugía ambulatoria Hospital de Alta Complejidad Virgen de la Puerta Essalud - Valdivia Chumbe, Cinthia Katherine (2019)
The present investigation of cross-sectional descriptive correlation type was carried out with the patients who attend the ambulatory surgery service of the Virgen de la Puerta Essalud High Complexity Hospital between January and July 2018, the sample population consisted of 90 patients To whom an instrument divided into two parts was applied, the first on the socio-epidemiological factors and the second part on the management of coping with ambulatory surgery for statistical analysis, the statistical test of square che was used, reaching the following conclusions: 51.1 percent of patients in the preoperative phase are between the ages of 60 to 70 years old, 44.4 percent between the ages of 36 to 59 years and only 4.4 percent between 25 to 35 years of age, 55.5 percent one hundred were women and 44.4 percent men, the type of anesthesia programmed 76.6 percent was local and 23.3 percent to regional. 65.6 percent of preoperative patients showed adequate coping management and 34.4 percent inadequate. There is a statistically significant relationship between the appropriate management of coping and age P = 0.0168, but not with the sex and the type of anesthesia to be used.